El Rodeo, 1960 (1960)
Cover of the El Rodeo yearbook reflects a growing interest in aeronautical advancements. Find the fully scanned 1960 El Rodeo here: ua-pub_00000137 https://digital.lib.calpoly.edu/rekl-23258.